Legal nature of the contract for the supply of energy and other resources through joined network - Вавженчук, Сергій Ярославович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
The article focuses on a series of aspects of legal regulation and clarification of individual problems ofthe essence of contract for the supply of energy and other resources through joined network. It pays particular attention to the subject of such contract.